Silicon photomultipliers and their applications for detection of light - Dagarin, Miha (Matrika, 2020)
Silicon photomultiplier is a detector capable of detecting single-photon events. Its predecessors PIN and Avalanche photodiodes do not posses that ability; a Photomultiplier tube, while possessing that ability, has other disadvantages. This article deals with the evolution of photosensors from PMTs to SiPMs, differences in their construction and properties. As SiPMs have high noise signals, some solutions to minimize their impact on measurements are presented. At the end some applications using SiPMs are listed.
Keywords: detektorji fotonov; photosensors; silicijeve fotopomnoževalke; silicon photomultipliers